Thermochronologic constraints on Late Cretaceous to Cenozoic exhumation of the Bendeleben Mountains, Seward Peninsula, Alaska - Kalin T. McDannell; Jaime Toro; Jeremy K. Hourigan; Daniel Harris (Geochemistry, Geophysics, Geosystems)
Abstract In the Bendeleben Mountains, Seward Peninsula, mid‐Cretaceous granites are exposed in an uplifted block bounded on its south side by an E‐W striking normal fault. The Bendeleben fault has well‐preserved scarps 4–7 m in height that offset Holocene moraines. Seismic activity, young normal faulting, and Quaternary basaltic volcanism are all evidence of active extension. South of the Bendeleben fault, there is a 3–4 km deep basin. Fifteen apatite (U‐Th)/He ages from granitic samples of the footwall yield an Eocene weighted mean age of 41.3±4.8 Ma. Biotite 40Ar/39Ar ages from the country rock of the Bendeleben pluton are 81–83 Ma. In spite of the young fault scarps, HeFTy and Pecube thermal modeling results illustrate that rapid exhumation of the Bendeleben Mountains occurred in the Late Cretaceous‐Eocene and slowed since the Oligocene. A weak age‐elevation relationship of apatite He ages and a lack of correlation between age and distance from the fault indicate that exhumation was accomplished with minimal block rotation on a steeply dipping, long‐lived normal fault. Timing of extension in the Seward Peninsula can be correlated with deformation in the offshore Hope Basin where seismic reflection lines document Early Tertiary large‐magnitude normal faulting followed by minor post‐Miocene reactivation. The faulting observed in the Bendeleben Mountains is part of an extensional system that spans a large portion of the Bering Strait region. The tectonic model proposed in previous studies suggests that clockwise rotation of the Bering block relative to North America is the cause of extensional deformation in western Alaska.